Bull Trout (Salvelinus confluentus) Population Structure and Extent of Hybridization with Brook Trout (S. fontinalis) Across Alberta's Eastern Slopes - Franks, Emily (Peer Beyond Graduate Research Conference, 2025)
Biodiversity loss on Earth is increasing, primarily from anthropogenic (human) impacts and the threat of climate change. Native bull trout (Salvelinus confluentus) is one species in Alberta that are currently threatened and require conservation action to survive. To aid in species management goals, we performed a genetic analysis on fish samples across the province. This was performed to determine the extent non-native hybridization, and the genetic population structure of bull trout across Alberta.